Analisis Peranan Penting Etika Bisnis Dalam Kelangsungan Usaha Perusahaan Bisnis - Devi Widiyawati (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
This study aims to determine the role of business ethics in the continuity of a business enterprise. This research uses the library research method, where the study is based on the opinions of an expert on business ethics and corporate business continuity, by collecting secondary data or using data that has been recorded, both in the form of reports and the results of previous research. . This business ethics is implemented for various aspects. Maintaining mutual trust in cooperation will greatly affect the reputation of the company, both at the micro and macro levels. All of this does not provide immediate benefits, but this is a form of long-term investment for all elements of the business environment.